Leadership Management of the Prophet Muhammad SAW and Its Relationship with Islamic Education Management - Fathih, Muhammad Amin; Muhlis, Nur Khozim; Yahya, Minhad Ali (Eduprof : Islamic Education Journal, 2024)
The role and function of leadership in an educational institution are the main factors in realizing the achievement of the vision and mission of education. However, a leader will not be able to carry out his roles and functions to the fullest, if the leader is not able to maximize his leadership management properly. The practice of leadership management of the Prophet Muhammad or often termed prophetic leadership is one form of leadership that should be used as an example for today's leaders. His success in bringing Islam into one of the largest religions in the world and in fostering high character behavior towards his people. It is a testament to his success in carrying out his leadership role. The form of application of management functions in the leadership of the Prophet Muhammad can be seen from the strategic planning of da'wah which began by analyzing the situation and conditions at that time, where da'wah in Mecca was carried out secretly while in Medina it was carried out openly. Meanwhile, in the success of his vision and mission, he focused his da'wah in Mecca on fostering monotheism and morals which was then followed by da'wah in Medina by focusing on political and social development. His prophetic leadership was applied to his four prophetic traits, namely shiddiq, amanah, tablik and fatonah. Where these four traits become an important aspect for Islamic educational institutions in applying a leadership model that always prioritizes honesty, trustworthiness, tablik (always conveys what must be conveyed), fatonah (has emotional and intellectual intelligence) in determining a policy or decision. and always cultivate the nature of obedience to Islamic values